EFFECT OF CATAMARAN HULL TYPE ON OCEAN WASTE COLLECTION BEHAVIOR - Sugianto, Erik; Zamzami, Rifqi Akmal; Winarno, Arif; Prasutiyon, Hadi (Journal of Marine-Earth Science and Technology, 2022)
In this paper an attempt has been made to assess how effective waste-collecting use catamaran ship with conveyor in the front. Numerical investigation based on Reynolds Averaged Navier Stokes (RANS) for predicting the flow pattern characteristics, velocity contour, and ship resistance. The focus of the present study is the impact of catamaran ship hull front shape on waste collection in calm water through the numerical methods. The three variations of the front of the hull used are symmetrical hull type, inner flat, and outer flat. It is done using speed variations of 1 to 4 knots. The results show inner flat hull catamaran has the smallest total resistance value than others. In addition, analysis of the flow pattern in front of catamaran shows that outer flat hull catamaran is the easiest to make waste closer to conveyor. From analysis of velocity contours shows that outer flat hull catamaran also has fastest to make the waste close to conveyor.